Revitalisasi tongkonan sebagai daya tarik wisata dalam upaya peningkatan ekonomi masyarakat desa wisata Kole Sawangan - Astriwati Biringkanae; Rahma Gusmawati Tammu (Journal of Tourism and Economic, 2022)
The purpose of this study is to analyze and identify strategies through the Tongkonan revitalization program in increasing tourist attractiveness in the Kole Sawangan Tourism Village in a sustainable manner. Sources of data in this study were obtained through interviews, observations, and documentation. The results of the research show that the determination of strategies based on the results of the SWOT analysis in the Kole Sawangan Tourism Village. Determining strategies as much as possible to be able to optimally increase and empower the tourism potential in the Kole Sawangan Tourism Village so that it will encourage an increase in the economic level of the community.